Patient-reported outcome measures as an outcome variable in sports medicine research - Snyder Valier, Alison R.; Huxel Bliven, Kellie C.; Lam, Kenneth C.; Valovich McLeod, Tamara C. (Frontiers in Sports and Active Living, 2022)
Injury prevention and rehabilitation research often address variables that would be considered clinician-oriented outcomes, such as strength, range of motion, laxity, and return-to-sport. While clinician-oriented variables are helpful in describing the physiological recovery from injury, they neglect the patient perspective and aspects of patient-centered care. Variables that capture patient perspective are essential when considering the impact of injury and recovery on the lives of patients. The inclusion of patient-reported outcome measures (PROMs) as dependent variables in sports medicine research, including injury prevention and rehabilitation research, provides a unique perspective regarding the patient’s perception of their health status, the effectiveness of treatments, and other information that the patient deems important to their care. Over the last 20 years, there has been a significant increase in the use of PROMs in sports medicine research. The growing body of work gives opportunity to reflect on what has been done and to provide some ideas of how to strengthen the evidence moving forward. This mini-review will discuss ideas for the inclusion of PROMs in sports medicine research, with a focus on critical factors, gaps, and future directions in this area of research. Important elements of research with PROMs, including instrument selection, administration, and interpretation, will be discussed and areas for improvement, consideration, and standardization will be provided.